2001
DOI: 10.1046/j.1365-2486.2001.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific responses of plant communities to altered carbon and nutrient availability

Abstract: Summary In a field microcosm experiment, species‐specific responses of aboveground biomass of two California annual grassland communities to elevated CO2 and nutrient availability were investigated. One community grows on shallow, nutrient‐poor serpentine‐derived soil whereas the other occurs on deeper, modestly fertile sandstone/greenstone‐derived substrate. In most species, CO2 effects did not appear until late in the growing season, probably because the elevated CO2 increased water‐use‐efficiency easing, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…The reason for the dependency of the CO 2 effects from soil types might be that the availability of nutrients becomes limiting for one of the species under elevated CO 2 (here beech), while for the other (here spruce), the nutrient supply is still adequate. The increasing nutrient limitation under CO 2 enrichment for beech might be either imposed by the larger CO 2 sensitivity of the competitor (spruce) or it might be caused indirectly by a greater nutrient immobilization at elevated CO 2 (Joel et al 2001). However, under adequate resource availability (here on the calcareous sand), the response of tree species to CO 2 enrichment depends solely on the responsiveness of each tree species itself.…”
Section: Soil-dependent Co 2 Effects On Nutrient Accumulation In Beecmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for the dependency of the CO 2 effects from soil types might be that the availability of nutrients becomes limiting for one of the species under elevated CO 2 (here beech), while for the other (here spruce), the nutrient supply is still adequate. The increasing nutrient limitation under CO 2 enrichment for beech might be either imposed by the larger CO 2 sensitivity of the competitor (spruce) or it might be caused indirectly by a greater nutrient immobilization at elevated CO 2 (Joel et al 2001). However, under adequate resource availability (here on the calcareous sand), the response of tree species to CO 2 enrichment depends solely on the responsiveness of each tree species itself.…”
Section: Soil-dependent Co 2 Effects On Nutrient Accumulation In Beecmentioning
confidence: 99%
“…In diverse plant communities, the responsiveness of various plants to elevated CO 2 can be different, which may lead to changes in plant community composition and biodiversity (Leadley et al 1999;Körner 2000;Joel et al 2001). Differences in the species-level growth response to elevated CO 2 may be driven, by and large, by differences in the ability to acquire nutrients (Berntson et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many empirical studies have shown that V c,25 and J 25 correlate with leaf nitrogen content (e.g., Ryan 1995, Reich et al 1998, Medlyn et al 1999, Kattge et al 2009, Rogers 2014 and this relationship forms the basis of many ESM estimations of V c,25 (Kattge et al 2009, Rogers 2014 and J 25 (Kattge and Knorr 2007). Variation in V c,25 and J 25 is substantial (Wullschleger 1993, Medlyn et al 1999) and occurs with growth conditions (Reich et al 1998, Cai et al 2007, season (Wilson et al 2000, and among species (Wohlfahrt et al 1999, Joel et al 2001. In view of these large variations, it is well recognized that current ESM parameterization of V c,25 and J 25 oversimplifies the representation of this model input, and that refined representation of variables that control V c,25 and J 25 is critical for improving model simulations of landatmosphere carbon exchange (Bonan et al 2011, Bauerle et al 2012, Rogers 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The relative responsiveness of these 2 honey mesquite varieties to CO 2 enrichment may indicate which will more aggressively encroach into rangelands in the future. Previous investigations have identified speciesspecific (e.g., Joel et al 2001;Goverde et al 2002) and genotype-specific (e.g., Roumet et al 2002) responses of plants to CO 2 enrichment. Dissimilar growth responses to CO 2 for these 2 honey mesquite varieties may be manifested in differential rates of shrub encroachment in arid and more mesic rangelands (Polley 1997;Polley et al 1997).…”
Section: Introductionmentioning
confidence: 99%